Futebol de várzea como mediador cultural na comunidade São Gonçalo Beira Rio - Benitez, Allan Kardec Pinto Acosta (2014)
Considering Culture and Leisure Football bifurcations that engender social events in its many facets, the objective is to investigate mediation from the grassroots football of community in São Gonçalo Beira Rio in Cuiaba, Mato Grosso, having as a research methodology field through the collection of oral histories. In the context multifaceted and diagnostic context in which overlap identity and otherness, what role would the grassroots football in the mediation of local differences, ways to make your practice interact and modify the space and relationships? In this sense, this study is a slit that opens a possibility of multiplication and interconnection inter - territories, establishing bridges between borders. To this end, starting in search of paths or trajectories of ways to make teams of the São Gonçalo Beira Rio and Milionários Futebol Clube, charged us scrutinize, through oral interviews, accounts of the life history of these two great football team the grassroots. Concepts of space, territory , tactics and strategies, and oral reports , among others, offer theoretical support coming from various fields such as Cultural History, Anthropology, Sociology, Social Communication , Sport and Recreation, so they serve as a way of expanding various targeted, the multiplicity of lines that intersect and are lost, the multifaceted game that makes football of the grassroots. We talk about Deleuze cartography, many dimensions ways to make that change in the social space, which connect and disconnect in dimensions that community. To take into consideration the antagonistic force of the word "conclusion", introduced here as final thoughts possibility of openings on cultural mediation football of the grassroots has played in the community of São Gonçalo Beira Rio. Considering, also that in this twenty-first century the power of the local culture, everyday that highlights the social power struggles in the game, this game where identities and differences overlap so provocative in the art of acting in the contemporary world.